Pengaruh Budaya Strategis Amerika Serikat Terhadap Kebijakan Luar Negeri Barack Obama dan Donald Trump dalam Penyelesaian Konflik Suriah - Noviyanti, Noviyanti; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2020)
Barack Obama and Donald Trump are the president of the United States who has different political parties. Obama is from democratic party meanwhile Donald Trump is from republican party. In Syria conflict settlement, Obama and Trump both has several foreign policies. This reasearch aims to described how US strategic culture affects Barack Obama and Donald Trump foreign policy in Syria conflict settlement. This reasearch is using qualitative method. This reasearch is also using constructivism approach perceiving strategic culture. The result of this research is strategic culture has affects Barack Obama and Donald Trump foreign policy in Syria conflict settlement. The implication of evil vs good strategic culture is there US has reppresive policy to Bashar al Assad policy in Syria Conflict. The implication of exeptionalism strategic culture are the withdrawal of US in cooperation or international forum as well as threathening and attacking the Syrian Government